Effects of Leachates from UV-Weathered Microplastic in Cell-Based Bioassays - Rummel, Christoph D; Escher, Beate I; Sandblom, Oskar; Plassmann, Merle M; Arp, Hans Peter H; MacLeod, Matthew; Jahnke, Annika (Environmental science & technology, 2019)
Standard ecotoxicological testing of microplastic does not provide insight into the influence that environmental weathering by, e.g., UV light has on related effects. In this study, we leached chemicals from plastic into artificial seawater during simulated UV-induced weathering. We tested largely additive-free preproduction polyethylene, polyethylene terephthalate, polypropylene, and polystyrene and two types of plastic obtained from electronic equipment as positive controls. Leachates were concentrated by solid-phase extraction and dosed into cell-based bioassays that cover (i) cytotoxicity; (ii) activation of metabolic enzymes via binding to the arylhydrocarbon receptor (AhR) and the peroxisome proliferator-activated receptor (PPARγ); (iii) specific, receptor-mediated effects (estrogenicity, ERα); and (iv) adaptive response to oxidative stress (AREc32). LC-HRMS analysis was used to identify possible chain-scission products of polymer degradation, which were then tested in AREc32 and PPARγ. Explicit activation of all assays by the positive controls provided proof-of-concept of the experimental setup to demonstrate effects of chemicals liberated during weathering. All plastic leachates activated the oxidative stress response, in most cases with increased induction by UV-treated samples compared to dark controls. For PPARγ, polyethylene-specific effects were partially explained by the detected dicarboxylic acids. Since the preproduction plastic showed low effects often in the range of the blanks future studies should investigate implications of weathering on end consumer products containing additives.